Application of land administration domain model to recognition of indigenous community rights in the Philippines :laws examined with spatial dimensions - Hespanha, João (2020)
http://www.fig.net/resources/proceedings/fig_proceedings/fig2015/papers/ts04b/TS04B_hespanhaa_paixao_et_al_7579.pdf